Assessment of the impact of climate change on hydropower potential in the Nanliujiang River basin of China. (15th January 2019) - Wang, Hejia; Xiao, Weihua; Wang, Yicheng; Zhao, Yong; Lu, Fan; Yang, Mingzhi; Hou, Baodeng; Yang, Heng
Abstract: This study presents a model-based approach for assessing the impact of climate change on hydropower potential in the Nanliujiang River Basin of China. The variable infiltration capacity (VIC) hydrological model was proved to be able to do a good runoff simulation after 1000 times of calibration and validation, while it has greater uncertainty in the simulation of high flow and low flow. Coupling the VIC model with five climate models, the spatial and temporal distributions of water resources in the future are analyzed, and the uncertainty analysis shows that the multi-model ensemble results can more reliably reflect future climate change. Then, the hydropower potential of the whole river basin in the future is analyzed in order to allow for a more realistic picture of future hydropower planning. The results of this study indicate that, different degrees of future alterations in river discharge and the spatial and temporal distributions of water resources have to be expected, leading to an increase of 7.7%–15.6% in hydropower potentials under the scenario of RCP2.6, RCP4.5 and RCP8.5. Highlights: A VIC model coupled with five climate models is built in the Nanliujiang River basin. The spatial and temporal distributions of water resources in the future are analyzed. The uncertainty of hydrological model and climate change prediction results are analyzed. The hydropower potential of the whole river basin in the future is calculated.